Algoritmo de ordenamiento como apoyo a niños con TDAH mediante el desarrollo de videojuegos bilingues e interactivos. - Barahona Cevallos, Roberto Alejandro (2022)
Attention Deficit Hyperactivity Disorder (ADHD) involves a pattern of attention deficit, hyperactivity, and impulsivity. There are several works, where videogames are used as a technological support tool in the classroom. However, although the benefits are documented, it is not clear how it was created and especially the purpose of learning for which they were created, so the objec tive is: to make an application of the software named JaraSmart, in the use of ordering algorithm to support children with ADHD through the development of bilingual videogames. The results are encouraging and allowed us to establish a more formal basis for the use of bilingual videogames with the application of sorting algorithms as support for children with ADHD, aged 10 to 12 years.